Philosophical and methodological analysis of the problem of compulsory sources of law recognition - Sukhaparau, Viktar P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The problem of recognition of compulsory of law recognition of law at world-outlook, legal and politological sight is substantiated in the article. Being researched problem has important significance in the context of today’s convergenting and transforming processes of Roman German law system. Causes of sources of law recognition at world-outlook, legal and politological sight are revealed as well as a pattern of a post-state society is theoretically constructed. Criticism of classical liberalism provisions (T. Hobbes, J. Locke, G. Grotius et al.) has enabled the author to formulate another natural law substance having force in three social development conditions (natural, state, post-state). The author states constancy of a natural condition of a society in spite of the fact of transition to the state. Potential of judicial precedent as a source of law in Ro- man German law system is commented. The results of research contributes to complex understanding of the need to follow sources of law.
Keywords: source of law; source of law recognition; natural society; state; post-state society; natural law; liberty limitation; judicial precedent; legal political power; classical liberalism